1998
DOI: 10.1046/j.1523-5378.1998.08052.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Gastrointestinal Bleeding Associated with Helicobacter pylori Infection in Patients with Hemophilia or von Willebrand’s Syndrome

Abstract: The rate of H. pylori infection and dyspepsia in patients with bleeding disorders is similar to the prevalence in the normal population. Due to increased bleeding complications, H. pylori screening and therapy appears mandatory in patients with bleeding disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 13 publications
3
17
0
Order By: Relevance
“…In our group of haemophilic patients with upper gastrointestinal bleeding, H. pylori infection was diagnosed in 71.7%, whereas in patients with no bleeding history, the infection was found in 39.0% of the subjects. Similar results were reported by Braden et al who found 71% of H. pylori-positive patients with gastrointestinal bleeding, and 25% of H. pyloripositive patients with no history of bleeding episodes [19]. Upper gastrointestinal bleeding was statistically more frequent in H. pylori-positive patients with haemophilia than in the H. pylori-negative haemophilic patients (71.7% vs. 28.3%; P < 0.0002).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In our group of haemophilic patients with upper gastrointestinal bleeding, H. pylori infection was diagnosed in 71.7%, whereas in patients with no bleeding history, the infection was found in 39.0% of the subjects. Similar results were reported by Braden et al who found 71% of H. pylori-positive patients with gastrointestinal bleeding, and 25% of H. pyloripositive patients with no history of bleeding episodes [19]. Upper gastrointestinal bleeding was statistically more frequent in H. pylori-positive patients with haemophilia than in the H. pylori-negative haemophilic patients (71.7% vs. 28.3%; P < 0.0002).…”
Section: Discussionsupporting
confidence: 88%
“…As shown by comparative studies, the prevalence of H. pylori infection in the haemophilia population does not differ from the prevalence rate of infection with this bacterium in the general population [19,21]. However, the prevalence rate of upper gastrointestinal bleeding is statistically more significant in haemophilic patients than in those with no congenital coagulopathies [13,19,21]. The bleeding may result from small mucosal injuries because of the H. pylori pathogenic factors which do not manifest themselves clinically in patients with normal haemostasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of PWH, 10-25% experience episodes, of GI bleeding [6,11,12,[23][24][25][26] and recurrent bleeding is common. The widespread usage of clotting factor concentrates, H2 blockers and proton pump inhibitors have drastically reduced the high mortality reported in early studies when gastrointestinal haemorrhage was the most frequent cause of death [11].…”
Section: Discussionmentioning
confidence: 99%
“…These procedures are cost efficient for the health system, if one takes into account that the screening, followed by treatment of all infected patients, yields a reduction of direct costs over a 5-year period of 130 US$ per screened patient [265]. Therefore, due to increased bleeding complications, H. pylori screening and therapy appear mandatory in patients with bleeding disorders [266]. This conduct would also be applicable for patients undergoing prophylactic anticoagulation therapy [267] like aspirin [95].…”
Section: Other Hematologic Manifestationsmentioning
confidence: 99%